Stosowanie narzędzi badania ryzyka i wartości opcji realnych w projektach badawczo-rozwojowych w Polsce (wyniki badań) - Mielcarz, Paweł (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Capital budgeting of the R&D projects is one of the most important and difficult tasks that face the financial managers. During the process of decision making they should take into consideration both risk and value of real options included in such projects. The article presents summary of survey which tried to find out the answer to the question: What are the practices of R&D evaluation in the Polish biggest companies. The result clearly indicates that Polish companies do not use contemporary tools which are able to estimate value of flexibility. Decision makers still trust more their experience than analysis built on sophisticated methods. It proves that well recognized methods by the academic world are not common in the business environment. Based on the results of the survey, the author presents some conclusions and explanations to the existing situation. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1183, s. 284-299